Effect of ribose-glycated BSA on histone demethylation - Xi, Mengqi; Zhang, Lingyun; Wei, Yan; Li, Ting; Qu, Meihua; Hua, Qian; He, Rongqiao; Liu, Ying (Frontiers in Genetics, 2022)
A reducing sugar reacts with the protein, resulting in advanced glycation end-products (AGEs), which have been implicated in diabetes-related complications. Recently, it has been found that both type 1 and type 2 diabetic patients suffer from not only glucose but also ribose dysmetabolism. Here, we compared the effects of ribose and glucose glycation on epigenetics, such as histone methylation and demethylation. To prepare ribose-glycated (riboglycated) proteins, we incubated 150 μM bovine serum albumin (BSA) with 1 M ribose at different time periods, and we evaluated the samples by ELISAs, Western blot analysis, and cellular experiments. Riboglycated BSA, which was incubated with ribose for approximately 7 days, showed the strongest cytotoxicity, leading to a significant decrease in the viability of SH-SY5Y cells cultured for 24 h (IC50 = 1.5 μM). A global demethylation of histone 3 (H3K4) was observed in SH-SY5Y cells accompanied with significant increases in lysine-specific demethylase-1 (LSD1) and plant homeodomain finger protein 8 (PHF8) after treatment with riboglycated BSA (1.5 μM), but demethylation did not occur after treatment with glucose-glycated (glucoglycated) proteins or the ribose, glucose, BSA, and Tris–HCl controls. Moreover, a significant demethylation of H3K4, H3K4me3, and H3K4me2, but not H3K4me1, occurred in the presence of riboglycated proteins. A significant increase of formaldehyde was also detected in the medium of SH-SY5Y cells cultured with riboglycated BSA, further indicating the occurrence of histone demethylation. The present study provides a new insight into understanding an epigenetic mechanism of diabetes mellitus (DM) related to ribose metabolic disorders.